Construction of recombinant adenovirus Ad-rat PLCÎ³2 and its effects on apoptosis of rat liver cell BRL-3A in vitro - Chen, X; Lv, Q; Liu, Y; Deng, W (Cellular and Molecular Biology, 2016)
Although the role of PLCÎ³2 in apoptotic response has been reported, too little is known about whether PLCÎ³2 induces liver cell apoptosis during liver regeneration. Therefore, this study firstly packaged Ad-PLCÎ³2 recombinant adenovirus and primarily evaluated its effect on apoptosis of rat liver cell BRL-3A in vitro. Following ten days of co-transfection of pHBAd-MCMV-GFP-PLCÎ³2 and pHBAd-BHG into HEK293 cells, viral cytopathic effect (CPE) was apparent. Following three rounds of amplification, tissue culture infectious dose 50 (TCID50) assay showed that the titer value reached 1í—1010 PFU/mL. After 24 h of transfection of recombinant adenovirus into BRL-3A cells, transfection efficiency of adenovirus into BRL-3A cells was above 90% when obsereved under fluorescent microscopy. qRT-PCR and Western blot assays showed mRNA and protein levels of PLCÎ³2 were significantly elevated in the transfected BRL-3A cells. Flow cytometric analysis showed that, compared with the control and Ad-GFP groups, cell apoptosis rate of Ad-PLCÎ³2 group were significantly increased (P<0.01), and the cell cycle in Ad-PLCÎ³2 group was arrested at G1 phase which was manifested by a marked increase (P<0.01) in the percentage of G1 phase cells and a great decrease (P<0.01) in the percentage of S and G2/M phase cells. It was concluded from above results that recombinant adenovirus Ad-PLCÎ³2 was packaged successfully, and could promote cell apoptosis by arresting the transition from G1 to S phase of BRL-3A cells.